L’instrumentation de la démarche de professionnalisation par l’usage du carnet de bord en formation - Jean-Luc Denny; Brigitte Pagnani; Louis Durrive (Recherches en Éducation)
The article discusses the instrumentation of professionalization approaches through writing in university training systems. We are questioning how it contributes to the professionalism of actors in supporting students. The use of a logbook is mobilized by students enrolled in a university degree of "guidance the students" from the University of Strasbourg. Taking the ergological approach, which claims an anthropological approach to work, the data collection protocol mobilizes the semi-directive interview and the drawing as an artifact, two interviews are conducted with three participants. The results document a logbook initially full of strangeness that seems to makes learning difficult until it becomes a laboratory instrument through a dialogic process. The discussion defends a professionalization taken from the angle of a norms debate.